Kepemimpinan Pendidikan Islam - Ade Irvan Margolang; M Rezi Syahbanda Nst; Maidiana M (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Leadership in the education system has a very vital role, namely determining whether an organization will progress or not. Islamic educational leadership is a method used by leaders to influence, mobilize, motivate and direct people in educational institutions so that the implementation of education can be more efficient and effective in achieving planned educational goals. This research specifically aims to analyze discussions about Islamic Educational Leadership. In this research the author used a qualitative method with a library research approach. Library research is research that functions to obtain information from books, magazines, documents, historical records or in other words the facilities contained in the library.